2011
DOI: 10.1186/1472-6831-11-9
|View full text |Cite
|
Sign up to set email alerts
|

Age, period, and cohort analysis of regular dental care behavior and edentulism: A marginal approach

Abstract: BackgroundTo analyze the regular dental care behavior and prevalence of edentulism in adult Danes, reported in sequential cross-sectional oral health surveys by the application of a marginal approach to consider the possible clustering effect of birth cohorts.MethodsData from four sequential cross-sectional surveys of non-institutionalized Danes conducted from 1975-2005 comprising 4330 respondents aged 15+ years in 9 birth cohorts were analyzed. The key study variables were seeking dental care on an annual bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 70 publications
0
17
0
4
Order By: Relevance
“…Therefore, it was expected that this group of patients would have a better dental status than patients elsewhere in the country. However, this result was not observed, as only 63% of the participants in this study did not wear dentures, whereas 82·9% of Danish citizens above the age of 35 years were estimated in 2005 to not wear dentures (Li et al. 2011).…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, it was expected that this group of patients would have a better dental status than patients elsewhere in the country. However, this result was not observed, as only 63% of the participants in this study did not wear dentures, whereas 82·9% of Danish citizens above the age of 35 years were estimated in 2005 to not wear dentures (Li et al. 2011).…”
Section: Discussionmentioning
confidence: 56%
“…This result might be attributed to ageing, or simply reflect a common history of the particular cohort investigated . Previous studies of sequential cross‐sectional or longitudinal design have consistently found a cohort rather than a period effect in dental health care utilization across time . Focusing a single cohort, this panel study encompasses period and age effects, but cannot uniquely distinguish between those effects without making additional assumptions .…”
Section: Discussionmentioning
confidence: 99%
“…The majority (70% to 80%) are enrolled in a recall system, on the clinician's initiative [42]. In Denmark, dental attendance rates rose steadily to over 88% among the 35-to 75+ age group [27]. The increased use of regular dental visits from 74% (2005) to 81% (2014) of 35-to 74 year old Germans and the improvement in oral hygiene among seniors [23] might be responsible for raising the oral health status of adults in Germany over the last decade.…”
Section: Possible Reasons For Variations In System Performancementioning
confidence: 99%